Questa generazione non durerà…parérchomai in Mc 13,30 / Mt 24,34 / Lc 21,32 - Chiorrini, Elisa (2023)
It is known that the commonly shared meaning of Mark 13:30 and parallels ("This generation will not pass away…") poses problems. An alternative interpretation is proposed, which resolves the hermeneutic difficulties of the text at its root. The turning point is the interpretation of the verb παρέρχομαι, which in the passage in question has the meaning of "go forward / continue" or, in a temporal sense, "last", "continue to live". From this perspective, Jesus’ prophecy takes on the coherent meaning of: "This generation will not last until all these things have happened". The Itala, Vulgate, and Peshitta translations allow for this interpretation. This is also supported by the judgment given by Jesus on his contemporaries: they will not receive any signs regarding the Messiah except that of Jonah and therefore they will not be able to witness the premonitory signs of the parousia.